Draft Annual Plan 1979-80 Government of Meghalaya - Planning Commission (Planning Commission, 1979)
The Fifth Plan outlay for Meghalaya was fixed at Rs. 89.53 crores. This was, however, subject to further revision depending upon the actual requirement for the Kyrdenkulai Hydel Project. the Fifth Plan outlay of Rs. 89.53 crores included? provision of Rs. 13.78 crores for the Minimum Needs Programme. the actual outlay for the five year period 1974-79 was Rs. 104.02 crores and the estimated expenditure during the period is Rs. 102'66 crores. The actual outlay for the four year period of the Fifth Plan (1974-78) was Rs. 74.91 crores. the estimated expenditure during the period was Rs. 71.33 crores.
Government of Meghalaya Planning Department